(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
This article analyzes the normative discipline, previous and current, of the judicial disqualification – also referred to as recusal – , examining the criticism regarding this institute. Subsequently, it focuses on the absolute inviolability of such recusal and its irreversibility, highlighting the impossibility of complaint, by the part, in what regards the disqualification.